Maria Lai : Legarsi alla montagna - Lai, Maria; Berengo Gardin, Piero; Pontiggia, Elena; Pisu, Maria Sofia; Prunas, Renata; Brandinelli, Giulia; Moretti, Lucia; Gute, Charles (Milano : 5 Continents Editions, 2021)
The inhabitants of Italian artist Maria Lais hometown of Ulassai live surrounded by mountains and a theatre of rocks, far from Sardinias famous coastline. This book documents Lais best-known large-scale collective art project, Leggarsi alla Montagna (Bound to the Mountain) which took place over 3 days beginning on September 8th, 1981. Harkening back to a Sardinian legend of a young girl saved from death by chasing a blue ribbon out of a cave, the artist convinced the residents of Ulassai to tie their homes and the mountain together with 17 miles of blue ribbon. A symbolic act of communal unity, the process was tempered by personal conflicts and ancient family feuds, resulting in ribbon that was knotted (for friendship), wrapped tightly (for conflict), or hung with bread (for love). This combination of land art, performance art, and sculpture was captured at the time by renowned photographer Piero Berengo Gardin, in images that the artist has worked with watercolours and markers.
In Italian with most texts also in English.
boek
Keywords: Lai, Maria; Contemporary history -- The arts Fine and decorative arts